PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERUMAHAN DAN KAWASAN PERMUKIMAN KABUPATEN TEBO - Wiska, Mayroza (Jurnal Ilmiah Manajemen Emor (Ekonomi Manajemen Orientasi Riset), 2022)
Abstract The purpose of this study is to work motivation and simultaneous, partial work discipline on employee performance. The type of research in this study is associative with casual relationships, employing this research approach to quantitative methods. Research shows that motivation for performance is significant and that it selects a positive relationship toward an employee’s performance with t_(hitung )2,541 > t_tabel 2,064. Work discipline has a significant effect and has a direction of positive relationships to employee performance with F_(hitung )2,176 > F_(tabel )2,064. From a production of positive determinations mode by the motivation for work and the discipline of labor to the 2,10 while the remaining 4,58 are affected by other variables not studied in this study. So the discipline motivation and work diciplin have partially influence and simultaneously on the performance of employess, because the value t_(hitung >) t_(tabel )and the value F_(hitung )> F_(tabel )and has a direction of positive relationship. Keyword : Work ,Motivation, Discipline, Performance ,Employe